2005
DOI: 10.1016/j.febslet.2005.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant glycosylation of α‐dystroglycan causes defective binding of laminin in the muscle of chicken muscular dystrophy

Abstract: Dystroglycan is a central component of dystrophinglycoprotein complex that links extracellular matrix and cytoskeleton in skeletal muscle. Although dystrophic chicken is well established as an animal model of human muscular dystrophy, the pathomechanism leading to muscular degeneration remains unknown. We show here that glycosylation and laminin-binding activity of a-dystroglycan (a-DG) are defective in dystrophic chicken. Extensive glycan structural analysis reveals that Galb1-3GalNAc and GalNAc residues are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Though much remains unclear about WWP1Õs substrates, it has been demonstrated that WWP1 could interact with bdystroglycan, an important muscle protein consisting of membrane [30]. Abnormal glycosylation of a-dystroglycan in chicken muscular dystrophy was also reported [31]. Some E3s are known to recognize sugar chain [32][33][34], leading to the hypothesis that WWP1 might be able to recognize the sugar chain of a-dystroglycan and regulate the glycosylated molecules, and that insufficiently glycosylated a-dystroglycan, which originally requires degradation, accumulates and causes the disease because altered WWP1 can not recognize and degrade it.…”
Section: Discussionmentioning
confidence: 99%
“…Though much remains unclear about WWP1Õs substrates, it has been demonstrated that WWP1 could interact with bdystroglycan, an important muscle protein consisting of membrane [30]. Abnormal glycosylation of a-dystroglycan in chicken muscular dystrophy was also reported [31]. Some E3s are known to recognize sugar chain [32][33][34], leading to the hypothesis that WWP1 might be able to recognize the sugar chain of a-dystroglycan and regulate the glycosylated molecules, and that insufficiently glycosylated a-dystroglycan, which originally requires degradation, accumulates and causes the disease because altered WWP1 can not recognize and degrade it.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several human congenital muscular dystrophies are caused by mutations in glycosyltransferases that modify the unusual O-linked carbohydrate moieties that are found on DG (Cohn, 2005;Schachter et al, 2004). The loss of these carbohydrate modifications has been shown to disrupt DG binding to several ligands, including laminins (Kanagawa et al, 2005;Kim et al, 2004;Patnaik and Stanley, 2005;Saito et al, 2005). Like laminin deficiencies that cause MCD1A, these dystrophies also cause developmental brain abnormalities, including MDC1C (myd in mice), Fukuyama's muscular dystrophy (FCMD), muscle-eye-brain disease (MEB) and Walker-Warburg syndrome (WWS).…”
Section: Discussionmentioning
confidence: 99%
“…The observed level of heterogeneity in the satellite cell population may relate to differences in experimental design, the timing Laminin is one of the external matrix proteins that is complexed with the dystrophin-associated proteins that are either internal, transmembrane or linked with proteins inside the sarcolemma in normal muscle (Crawford et al, 2000;Ervasti and Campbell, 1993;Ferletta et al, 2003). In muscles affected by mutations in proteins of the dystrophin-associated protein complex, the expression of laminin is reduced; this is also noted in dystrophin-deficient muscle (Ferletta et al, 2003;Kanagawa et al, 2005;Kikkawa et al, 2004;Kim et al, 2004;Saito et al, 2005). Treatment with glucocorticoids increases the expression of laminin in mdx mouse skeletal muscle (Anderson et al, 2000).…”
Section: Satellite Cells In Muscle Plasticitymentioning
confidence: 99%